Efeito da Suplementação da Vitamina C em Rações de Crescimento de Piau Três Pintas (Leporinus reinhardit) - Lutken, 1874 - Silva, Jaqueline Maria da (2009)
The objective of this study was to evaluate the influence of vitamin C supplementation in the diet of fish species piau três pintas (L. reinhardit), which was held to monitor the performance and yield production, analysis of the nutritional composition (carcass and fillet ), and glycemic parameters. The experiment lasted 90 days (fingerlings/ juvenile). 1040 fingerlings were used, housed in 16 tanks for breeding, with a capacity of 500 liters. The design was randomized blocks with four treatments and four replications, and the control diet was designed to meet the requirement of vitamin C as trade recommendations and other diets were prepared to contain levels of extra dietary supplementation of vitamin C (250; 500 and 750 mg ascorbic acid / kg diet). For the analysis of the nutritional composition were used 6 fish per experimental unit. All diets were isonitrogenous and isocaloric (28% PB and 3100 kcal / kg diet). No effect was observed significant regression in performance and glycemic parameters in supplementation levels of vitamin C. However, the fillet yield linearly decreasing the effect of treatments (р<0.05). Regarding the chemical composition of nutritional was observed in effect response to significant levels of supplementation and in some cases equating to the control. Thus, we observed increased linearly on the concentration of mineral matter (р<0.05) and decreasing trend for levels of energy rude (р<0.05). Therefore, it is concluded that the conditions of this work, the inclusion of vitamin C in commercial level was sufficient to provide productive performance benefits for chemical composition and nutritional stress reduction management and harvesting, equal to those diets that were supplemented.